Unsuspected severe tracheal stenosis and tracheomalacia after correction surgery for congenital scoliosis: A case report. Issue 2 (20th November 2022) - Wang, Shengru; Li, Ziquan; Guan, Wenmin; Zhang, Jianguo
Abstract: Tracheal stenosis and tracheomalacia in patients with congenital scoliosis are serious and rare conditions caused by congenital dysplasia, postintubation injury, trauma, and tracheal tumor. Anesthesia of a child with tracheal stenosis is challenging for anesthesiologists. We describe an 8‐year‐old female patient developed severe tracheal stenosis and tracheomalacia after growing rod implantation for congenital scoliosis. Comprehensive assessment of preoperative pulmonary function and airway morphology, which can be neglected clinically, should be performed in congenital scoliosis patients.